PERAN PONDOK PESANTREN DARUL KAMAL NAHDLATUL WATHAN DALAM MENDORONG PEMBANGUNAN PENDIDIKAN ISLAM DI PEDESAAN - Halimatuzzahrah; Sunardi (re-JIEM (Research Journal of Islamic Education Management), 2025)
This study examines the role of Darul Kamal Nahdlatul Wathan Islamic Boarding School as a driving force for the development of Islamic education in Kembang Kerang Daya Village, East Lombok, West Nusa Tenggara. The research employs a qualitative approach with a case study methodology through interviews, observations, and documentation. The findings demonstrate that Darul Kamal has successfully integrated religious education with practical life skills relevant to rural communities by providing formal education through madrasah and non-formal programs such as regular religious gatherings and Islamic courses, thereby offering flexible educational access to the community. Despite facing challenges related to limited infrastructure and management, Darul Kamal creates inclusive education by involving community leaders and the village government. The synergy between the institution and community fosters a strong sense of ownership, supports program sustainability, and generates positive impacts on rural socio-economic development. This research contributes to strengthening awareness of the urgency of Islamic education and developing practical skills to improve the quality of life in rural communities sustainably.